PRACTICE OF MANGREWA BUSINESS IN MALIBA HAMLET, CURIO DISTRICT, ENREKANG REGENCY ANALYSIS OF ISLAMIC ECONOMIC LAW - Mirnasari; Trimulato; Nuringsih; Syarifuddin (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
This research was conducted to know how Islamic Economic Law views Mangrewa Business Practices in Maliba Hamlet, Curio District, Enrekang Regency, South Sulawesi. The type of research conducted is field research with a qualitative model. The object of research is focused on the practice of Mangrewa business profit sharing in Maliba Hamlet, Curio District, Enrekang Regency. The nature of this research is descriptive, describing how the Mangrewa business practices are carried out by the local community and then associated with Islamic Economic Law which refers to the Qur'an and Hadith. Data collection techniques in this study are observation, interview, and documentation. The data analysis technique used is Qualitative Descriptive Analysis. The results showed that the Mangrewa business practice uses the principle of profit sharing with the use of the Mudharabah Mutlaqah contract where the owner of the capital gives livestock to the manager to be cared for without any specified time limit and the distribution of profits is carried out after the livestock produces children. Regarding using livestock as business capital, it is considered valid according to Islamic Economic Law because the form and amount are clear and can be delivered when Ijab Qabul. Then in terms of profit sharing, it is also permissible because it is by the principles of Islamic Economic Law in which the profit is divided equally without any party being disadvantaged, and there is an element of mutual consent from both parties.